Faktor Risiko Maternal yang Memengaruhi Kejadian Preeklamsia di RSU Rahmad Hidayah Provinsi Sumatera Utara - Marta Armita Silaban; Dear Megawati Situmorang (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The Development of the Research and Health Agency of the Ministry of Health explained that the largest cause of AKI in Indonesia is 32.4% hypertension and/or preeclampsia and 20.3% of postpartum hemorrhage. Hypertension in pregnancy is the main cause of direct death in Indonesia at this time. Severe preeclampsia is a condition where blood pressure is >160/110 mmHg at >20 weeks gestational age without seeing proteinuria and accompanied by involvement of other organs. Preeclampsia is also still a problem, 10% of pregnant women worldwide suffer from preeclampsia, and is the cause of 76,000 maternal deaths and 500,000 infant deaths 566 each year. The purpose of this study is to find out the maternal risk factors that affect the incidence of preeclampsia at Rahmad Hidayah Hospital. The research method used a cross sectional with a sample of 60 mothers. The results of the study were that there was a correlation between the maternal age variable and the incidence of preeclampsia with a value of p=0.004 (α<0.05); There was a correlation between the maternal parity variable and the incidence of preeclampsia with a value of p=0.019 (α<0.05); There was a correlation between the variable history of hypertension/preeclamsia and the incidence of preeclampsia with a value of p=0.000 (α<0.05).